2019
DOI: 10.1371/journal.pone.0216390
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in women’s Olympic shooting and effects in performance

Abstract: In 2018, the Olympic shooting regulations were modified to increase the number of women’s shots from 40 to 60, equaling the number given to men. This research presented in this paper addresses two research issues: (1) has the performance of women’s shooting changed as a result of this increase in the number of shots? and (2) with the equalized number of shots in place, do women and men perform differently? This study included 292 shooters who competed in the 2016 and/or 2018 European Championships who all obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
5
22
0
Order By: Relevance
“…Normally, these performance differences (around 10%) are due to the genetic profile, which implies hormonal, anthropometrical and physiological differences [6]. In Olympic shooting, after the last regulatory changes made by the ISSF following the IOC committee advice regarding gender equality in sports [1,2] the need to investigate shooting performance in depth has been suggested [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Normally, these performance differences (around 10%) are due to the genetic profile, which implies hormonal, anthropometrical and physiological differences [6]. In Olympic shooting, after the last regulatory changes made by the ISSF following the IOC committee advice regarding gender equality in sports [1,2] the need to investigate shooting performance in depth has been suggested [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the shooting performance comparison between men and women, Mon-López, Tejero-González and Calero [3] revealed that men obtain better results in pistol shooting than women; however, there were no performance differences between men and women in rifle shooting. Similarly, Goldschmied and Kowalczyk [4] found no differences between gender in Olympic rifle events (air rifle and small-bore rifle), and Kemnitz et al [5] found no differences in military rifle shooting.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations